Ethnomathematics: Masons and construction processes in Bagua-Amazonas - Estela Urbina, Ronald Omar (2024)
The objective of this research was to deepen the understanding of ethnomathematics developed by masons in the Amazonian regions of Peru. To this end, the mathematical concepts implicit in the masons' practices were identified and analyzed, as well as to understand the role of culture and the natural environment in the configuration of this knowledge. The type of study was considered ethnographic, and consisted of gathering information through observation. A questionnaire was applied, with the purpose of evidencing the procedures carried out by the masons in the resolution of labor calculations using the fundamental operations (addition, subtraction, multiplication and division) of ethnomathematical origin. In the same way, scientific articles were reviewed. One of the key findings of this research is the integration of mathematical concepts in the labor practice of masons. It was observed how these workers use a wide range of concepts, from geometry to calculus, in the planning and execution of their daily tasks. This integration demonstrated that mathematics is not an abstract concept separated from everyday life, but a practical and tangible tool that is used effectively to solve concrete problems.